1981
DOI: 10.1007/bf02354827
|View full text |Cite
|
Sign up to set email alerts
|

Cultured human skin fibroblasts: a model for the study of androgen action

Abstract: Human skin may be considered as a target organ for androgens, as are male sex accessory organs, since all events involved in testosterone action have been observed in this tissue. As a corollary, the mechanism of androgen action can be studied in vitro in cultured skin fibroblasts. The advantages of this system are that studies can be performed with intact human cells under carefully controlled conditions, differentiated genetic and biochemical characteristics of the cells are faithfully preserved and the biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

1983
1983
2000
2000

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(32 citation statements)
references
References 69 publications
(74 reference statements)
2
30
0
Order By: Relevance
“…The characteristics of the nuclear uptake assay used in this study, which shows -40-50% of the binding sites found in the intact, whole cell, are in accord with published data (11,19). Also, the whole cell assay gives androgen binding characteristics for fibroblasts (15) and the MCF-7 cells that are also in good agreement with the results of others (21). Moreover, the results of the sucrose gradient analysis on nuclear extracts shown in Fig.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The characteristics of the nuclear uptake assay used in this study, which shows -40-50% of the binding sites found in the intact, whole cell, are in accord with published data (11,19). Also, the whole cell assay gives androgen binding characteristics for fibroblasts (15) and the MCF-7 cells that are also in good agreement with the results of others (21). Moreover, the results of the sucrose gradient analysis on nuclear extracts shown in Fig.…”
Section: Discussionsupporting
confidence: 90%
“…5). In contrast to an easily identifiable peak of radioactivity in the 4S region of the gradient for the nuclear extract of the normal cells that was eliminated by coincubation 20 (20,21) it is unlikely that using a higher salt containing solution to extract the nuclei would have significantly altered the results of the gradient analysis, since the amount of specific total radioactivity incorporated into the nuclei of the patients' cells is so low (Fig. 1 and Table I).…”
Section: Introductionmentioning
confidence: 95%
“…Among the 11 patients studied, 10 had severe hypospadias, in some instances associated with other genital abnormalities. We selected these patients in an attempt to avoid subtle abnormalities of the external genitalia.…”
Section: Discussionmentioning
confidence: 98%
“…Binding was assessed using (with minor modifications) the methods described by Brown et al (10,11). In brief, after incubation, the medium was removed, and the monolayers were washed three times with 5 ml ice-cold Tris-NaCl buffer (0.9% NaCl, 20 mM Tris-HCl, pH 7.4).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, their presence after prolonged in vitro growth suggests that these are intrinsic differences, rather than differences due to circulating hormones or differing regional influences. The potential stability of the steroid receptor complement of subcultured cells is exemplified by the consistent regional differences in androgen receptor density and androgen responsiveness of subcultured skin fibroblasts (Brown & Migeon 1981).…”
Section: Discussionmentioning
confidence: 99%